El valor jurídico de la persona humana - Castillo Córdova, Luis (2005)
A Law useless for the human being and life in society, it is not only an ineffectived but illegitimated Law. To detect and face that is necessary to ask if such a Law fits with the legal value of the human being and its rights (Human Rights or Fundamental Rights). At national and international legal stage, Fundamental Rights are considered as the source for freedom, justice and peace in the World, or the foundation of the political order and social peace; or the supreme aim of the State and the Society. If this is the meaning of Fundamental Rights then, political powers must be closed rooted with them, not only through their responsibility to recognize and protect them, but also through the task of promoting their full compulsory force. From this point of view, Fundamental Rights present themselves as absolute realities ahead the State.